Repugnance Management and Transactions in the Body - Healy, Kieran; Krawiec, Kimberly D. (American Economic Review, 2017)
Researchers have made progress in understanding the role of repugnance in transactions involving the human body. Yet, often, the focus remains on exchange between individuals and how they mentally cope (or not) with repugnance. But these exchanges also entail a “vertical” dimension in which organizational and state actors both directly manage repugnance and also limit the repugnance management tools available to the marketplace. Analyzing repugnance and its management as an organizational and regulatory problem, in addition to an individual one, suggests that a single, harmonized system of exchange in bodily goods is unlikely to emerge with the passage of time.